2010
DOI: 10.1088/0031-8949/2010/t140/014035
|View full text |Cite
|
Sign up to set email alerts
|

Full revivals in 2D quantum walks

Abstract: Recurrence of a random walk is described by the Pólya number. For quantum walks, recurrence is understood as the return of the walker to the origin, rather than the full-revival of its quantum state. Localization for two dimensional quantum walks is known to exist in the sense of non-vanishing probability distribution in the asymptotic limit. We show on the example of the 2-D Grover walk that one can exploit the effect of localization to construct stationary solutions. Moreover, we find full-revivals of a quan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…In general, the trapping in DTQWs is caused by the presence of flat bands in the quasi-energy spectrum of the walk [22], which naturally depends on the choice of the coin operator. It was shown that the spectra of all trapping two-dimensional DTQWs contain at least two such flat bands with a π difference between their quasienergies [24]. Finding trapping coins involves solving Eq.…”
mentioning
confidence: 99%
“…In general, the trapping in DTQWs is caused by the presence of flat bands in the quasi-energy spectrum of the walk [22], which naturally depends on the choice of the coin operator. It was shown that the spectra of all trapping two-dimensional DTQWs contain at least two such flat bands with a π difference between their quasienergies [24]. Finding trapping coins involves solving Eq.…”
mentioning
confidence: 99%
“…in Ref. [17], [18], [1] and others. In this case also the distribution of the probability of finding the particle spreads away from the centre in general.…”
Section: Introductionmentioning
confidence: 86%
“…Any part of the initial state that has an overlap with these states will not participate in the otherwise ballistic spreading. The existence of the trapped states is due to the following pairs of eigenstates of the unitary evolution operator [13] |ϕ ± x,y =…”
Section: Applicationsmentioning
confidence: 99%
“…(41) for the double line quantum walk. This saves a lot of effort in comparison with re-deriving these results from the corresponding definitions using techniques similar to [13].…”
Section: Applicationsmentioning
confidence: 99%